Translation Analysis of Expressive Speech Representing Politeness Strategy in Interrogation Speech Events in the Novel A Murder Is Announced - Irawan, Dede; Nababan, M.R.; Santosa, Riyadi; Djatmika (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Interrogation speech events are one of the series that occur during the process of collecting clues, information, evidence carried out between speakers in this case the investigator and several related parties such as witnesses, alleged perpetrators or suspects, and other associated parties to obtain information about a crime, the interrogation speech event can be found in several films, dramas, novel in the crime genre. The novel A Murder is Announced is a crime genre novel that talks about a murder case, to solve the case the main characters in this novel conduct investigations and or inquisitions in which in the process there are interrogation actions on related parties who are suspected of knowing and or being involved in the alleged murder incident. In carrying out the interrogation, the characters use illocutionary speech acts to solve the murder case in the novel. The interrogation actions include information excavation, fact-finding, clues, and emphasis. From the interrogation, actions, several expressive speech acts, and politeness strategies were used to respond to the investigators' questions. In the context of research on expressive speech translation, the use of translation techniques is analysed to determine whether there is a shift due to the impact of the use of translation techniques. This study uses a qualitative descriptive method, with the aim of this study being to describe the use of expressive speech, politeness strategy, and translation techniques.